SN2018kzr: A Rapidly Declining Transient from the Destruction of a White Dwarf - Owen R. McBrien; Stephen J. Smartt; Ting-Wan Chen; Cosimo Inserra; James H. Gillanders; Stuart A. Sim; Anders Jerkstrand; Armin Rest; Stefano Valenti; Rupak Roy; Mariusz Gromadzki; Stefan Taubenberger; et al. (IOP PUBLISHING LTD, 2022)
We present SN2018kzr, the fastest declining supernova-like transient, second only to the kilonova, AT2017gfo. SN2018kzr is characterized by a peak magnitude of Mr = -17.98, a peak bolometric luminosity of ?1.4 & xfffd;& x5e0;10(43) erg s(?1), and a rapid decline rate of 0.48 & xfffd;& xfffd;0.03 mag day(?1) in the r band. The bolometric luminosity evolves too quickly to be explained by pure Ni-56 heating, necessitating the inclusion of an alternative powering source. Incorporating the spin-down of a magnetized neutron star adequately describes the lightcurve and we estimate a small ejecta mass of M-ej & xfffd;=& xfffd;0.10 & xfffd;& xfffd;0.05 M. Our spectral modeling suggests the ejecta is composed of intermediate mass elements including O, Si, and Mg and trace amounts of Fe-peak elements, which disfavors a binary neutron star merger. We discuss three explosion scenarios for SN2018kzr, given the low ejecta mass, intermediate mass element composition, and high likelihood of additional powering?the core collapse of an ultra-stripped progenitor, the accretion induced collapse (AIC) of a white dwarf, and the merger of a white dwarf and neutron star. The requirement for an alternative input energy source favors either the AIC with magnetar powering or a white dwarf?neutron star merger with energy from disk wind shocks.